Penerapan Metode Simple Addictive Weighting (SAW), Metode Weighted Product (WP), dan Technique for Order Preference by Similarity To Ideal Solution (TOPSIS) Dalam Pemberian Reward Kepada Karyawan - Aini Salsabila; Alifia Puspaningsih; Muhamad Hasbi Hasidiqi; Fatiah Amelia; Perani Rosyani (CV. Multi Kreasi Media, 2023)
Giving rewards to employees is one way to increase morale and improve performance for employees who excel. At the Financial and Asset Management Agency. However, there are several criteria that are also considered in awarding rewards. So we need a decision support system to help the selection of the best employees. In this study, 3 methods were selected, namely SAW (Simple Additive Weighting), Weighted Product (WP) Method, and Technique For Order Preference By Similarity To Ideal Solution (TOPSIS) which was carried out by giving weighting to each criterion that was assessed per individual employee. The criteria that were also assessed in this study were workload, attendance, discipline and salary requirements. The final result will be selected 1 best employee who gets the greatest value and is entitled to a reward.